For this case, the first thing we must do is define variables:
x: unknown number (1)
y: unknown number (2)
We now write the equations that model the problem:
their sum is 6.1:
![x + y = 6.1 ](https://tex.z-dn.net/?f=x%20%2B%20y%20%3D%206.1%0A)
their difference is 1.6:
![x - y = 1.6 ](https://tex.z-dn.net/?f=x%20-%20y%20%3D%201.6%0A)
Solving the system we have:
We add both equations:
![x + x = 6.1 + 1.6 2x = 7.7 x = 7.7 / 2 x = 3.85](https://tex.z-dn.net/?f=x%20%2B%20x%20%3D%206.1%20%2B%201.6%0A%0A2x%20%3D%207.7%0A%0Ax%20%3D%207.7%20%2F%202%0A%0Ax%20%3D%203.85)
Then, we look for the value of y using any of the equations:
Answer:
The numbers are:
Solution for x^2+5x=150 equation:
<span>Simplifying
x2 + 5x = 150
Reorder the terms:
5x + x2 = 150
Solving
5x + x2 = 150
Solving for variable 'x'.
Reorder the terms:
-150 + 5x + x2 = 150 + -150
Combine like terms: 150 + -150 = 0
-150 + 5x + x2 = 0
Factor a trinomial.
(-15 + -1x)(10 + -1x) = 0
Subproblem 1Set the factor '(-15 + -1x)' equal to zero and attempt to solve:
Simplifying
-15 + -1x = 0
Solving
-15 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '15' to each side of the equation.
-15 + 15 + -1x = 0 + 15
Combine like terms: -15 + 15 = 0
0 + -1x = 0 + 15
-1x = 0 + 15
Combine like terms: 0 + 15 = 15
-1x = 15
Divide each side by '-1'.
x = -15
Simplifying
x = -15
Subproblem 2Set the factor '(10 + -1x)' equal to zero and attempt to solve:
Simplifying
10 + -1x = 0
Solving
10 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-10' to each side of the equation.
10 + -10 + -1x = 0 + -10
Combine like terms: 10 + -10 = 0
0 + -1x = 0 + -10
-1x = 0 + -10
Combine like terms: 0 + -10 = -10
-1x = -10
Divide each side by '-1'.
x = 10
Simplifying
x = 10Solutionx = {-15, 10}</span>
Answer:
200g plain flour
150g almonds
225g sugar
150g butter
Step-by-step explanation:
80g÷4×10
60g÷4×10
90g÷4×10
60g÷4×10
4÷4×10
The best option is to multiply them together, there would be no value that is common between the two, (2m - 1)(2m + 5), and leave it in this form.
However, there is a second method.
Notice how between the two sits a difference of 6.
You can manipulate one of the fractions to render the same denominator and work from there.